WORK LIFE BALANCE DAN WORK ENGAGEMENT : PERAN MEDIASI KEPUASAN KERJA DALAM MENGHADAPI ERA NEW NORMAL - Mokhammad Khukaim Barkhowa; Tri Widodo; Muhamad Fauzi Fahlefi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
The Indonesian Ministry of Health has issued a Minister of Health Decree on Guidelines for the Prevention and Control of Covid-19 in Office and Industrial Workplaces in Support of Business Continuity in Pandemic Situations. The Minister of Manpower issues a Circular which states for companies that limit their business activities due to the policies of their respective local governments in preventing and overcoming COVID-19, causing some or all workers not to come to work, taking into account business continuity, changes in the amount and method of payment wages are made in accordance with the agreement between the employer and the worker. The purpose of this study was to analyze the effect of work-life balance on work engagement through job satisfaction as an intervening variable. Sampling in this study using the Slovin formula amounted to 100 respondents using simple random sampling technique. Data analysis using simple linear regression model, multiple and single test. The results of hypothesis testing work life balance statistically have a positive and significant effect on job satisfaction, job satisfaction is statistically positive and significant impact on work engagement, work life balance has an effect on work engagement through job satisfaction as an intervening variable.